An Unusual Presentation of Herpes Simplex Virus Encephalitis. (6th September 2012) - Boyapati, Ray; Papadopoulos, George; Olver, James; Geluk, Michael; Johnson, Paul D. R.
Abstract : We present a case of a 65-year-old man with an acute alteration in mental state that was initially diagnosed as a functional psychiatric condition. After extensive workup, herpes simplex virus type 1 (HSV-1) was detected in the patient's cerebrospinal fluid (CSF) by polymerase chain reaction (PCR), and he responded rapidly to treatment with acyclovir. The case illustrates the importance of actively excluding organic causes in such patients, the need to have a low threshold of suspicion for HSV encephalitis, and the central role of CSF PCR testing for the diagnosis of HSV encephalitis, even in the absence of CSF biochemical abnormalities.